Non-iatrogenic traumatic isolated bilothorax in a cat. Issue 1 (June 2017) - Mullins, Ronan A; Barandun, Marc A; Gallagher, Barbara; Cuddy, Laura C
Case summary: A 6-month-old spayed female domestic shorthair cat presented for evaluation of suspected bite wounds over the right caudal thorax and left cranial flank. Thoracic radiographs identified a mild right-sided pneumothorax, a small volume of right-sided pleural effusion, with increased soft tissue opacity in the right cranial and middle lung lobes. Abdominal ultrasound identified a very small gall bladder and several small pockets of free peritoneal fluid. Cytological analysis of peritoneal fluid was consistent with a modified transudate. Following initial diagnostic investigations, yellow–orange fluid began to emanate from the right-sided thoracic wound. Biochemical analysis of this fluid was consistent with bile. Exploratory coeliotomy revealed a right-sided radial diaphragmatic tear, with herniation of the quadrate liver lobe and a portion of the gall bladder into the right pleural space. The gall bladder was bi-lobed and avulsion of a single herniated lobe resulted in leakage of bile into the right pleural cavity, without concurrent bile peritonitis (biloabdomen). The cat underwent total cholecystectomy and diaphragmatic defect repair and recovered uneventfully. Relevance and novel information: To our knowledge, at the time of writing non-iatrogenic isolated bilothorax without concurrent biloabdomen has not been previously reported in the cat. This case highlights the importance of thorough assessment of cats with seemingly innocuous thoracic bite wounds. Despite the rarity of its occurrence, bilothorax should be considered a differential in cats with pleural effusion, even in the absence of bile peritonitis. We believe that the optimal treatment of cases of bilothorax is multifactorial and should be determined on a case-by-case basis.